In-vivo kinematic assessment of alloplastic temporomandibular joint replacements by means of helical axis: A cohort study with historical control. (9th June 2021) - Zumbrunn Wojczyńska, Aleksandra; Markova, Michala; Ettlin, Dominik A.; Gallo, Luigi M.; Colombo, Vera
Abstract: Alloplastic total temporomandibular joint replacement (TJR) is a surgical procedure used to restore normal mandibular function when conservative therapies fail. The instantaneous helical axis (HA), is a mathematical model used to visualize globally rigid body kinematics. It can be applied to mandibular motion for quantification of movement patterns and irregularities. Aim of this study was to analyze HA pathways in subjects with unilateral and bilateral TJR and compare them to a control group. An optoelectronic system was employed to track mouth opening/closing cycles (n = 3) of 15 patients (7 operated unilaterally, 8 bilaterally, 11 F, aged 24–72) and 12 controls (6 F, aged 23–40). HA position in space was determined for 30 equally-distributed steps of the observed movement. Total mandibular rotation around HA (Φtot ) and total translation along HA (Ttot ) were determined. Angles between HA and the anatomical coordinate system of the head (θx, θy, θz ); global fluctuation of HA spatial orientation (θe ), distance between condylar center (CP) and HA (dCP ) and its projections on the axes (xdCP, ydCP, zdCP ) were calculated. Overall, Φtot was larger in controls than in bilaterally operated subjects (p = 0.002, p = 0.003) and θz was larger in unilaterally operated subjects than in controls (p = 0.004) and bilaterally operated subjects (p = 0.002, p = 0.024). During opening, θ e ¯ was smaller in controls than in unilaterally operated subjects (p = 0.01). The distance dCP was smaller for alloplastic joints than for controls (p < 0.01 overall). In conclusion, mandibular HA pathways in patients with TJR differ significantly from controls in terms of spatial location and variability.